Koumiss and immunity: A thorough investigation of fermentation parameters and their impact on health benefits - Istanbullugil, Fatih Ramazan; Risvanli, Ali; Salikov, Ruslan; Bayraktar, Metin; Zhunushova, Aidai; Acaroz, Ulas; Uz, Muhammet (Elsevier Science Inc, 2024)
The aim of this study was to determine the components and cytokine and immunoglobulin levels of koumiss during different fermentation periods, and to reveal the interrelation between these parameters. For achieving this objective, 10 samples of koumiss were prepared and randomly divided into 2 groups: the first group was sampled at 0, 1, 5, 12, and 24 h of incubation at room temperature for analysis. The second group was stored at counts of Enterobacteriaceae spp., Staphylococcus, and Micrococcus spp. progressively decreased with the period of fermentation until becoming undetectable in the final samples of both groups. We fond positive or negative correlations between cytokine and immunoglobulin levels and the physicochemical and microbiological different fermentation times and temperatures does not concentrations.
Keywords: koumiss composition; cytokine level; immunoglobulin; microbiological analysis; physico chemical properties